Quantifying attention span across the lifespan - Simon, Alexander J.; Gallen, Courtney L.; Ziegler, David A.; Mishra, Jyoti; Marco, Elysa J.; Anguera, Joaquin A.; Gazzaley, Adam (Frontiers in Cognition, 2023)
Studies examining sustained attention abilities typically utilize metrics that quantify performance on vigilance tasks, such as response time and response time variability. However, approaches that assess the duration that an individual can maintain their attention over time are lacking.Here we developed an objective attention span metric that quantified the maximum amount of time that a participant continuously maintained an optimal "in the zone" sustained attention state while performing a continuous performance task. In a population of 262 individuals aged 7-85, we showed that attention span was longer in young adults than in children and older adults. Furthermore, declines in attention span over time during task engagement were related to clinical symptoms of inattention in children. These results suggest that quantifying attention span is a unique and meaningful method of assessing sustained attention across the lifespan and in populations with inattention symptoms.